Pengaruh Faktor Faktor Kelas Sosial Gaya Hidup dan Daya Beli dalam Masyarakat - Muhammad Sa’dii Fathir; Muhammad Turhan Yani; Sarmini (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Past examination or related investigation is very important in exploratory or legitimate articles. Hypotheses and specificities regarding the relationship or impact between factors are strengthened by past or relevant exploration. This article examines the elements that impact Social Class, specifically: Way of Life, Social Class, and Purchasing Power in the public arena. The technique used in this writing is a survey writing. The reason for writing this article is to speculate the impact between factors that will be used in additional exploration. The consequences of writing this survey article are: 1) Way of Life impacts social class; 2) Social class impacts people's purchasing power.